Ответ:
Пошаговое объяснение:
y'= (4ctg(x))'+(3tg(x))'-(4)'=
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
y'= (4ctg(x))'+(3tg(x))'-(4)'=![-\frac{4}{sin^2(x)} +\frac{3}{cos^2(x)}-0= \frac{3}{cos^2(x)}-\frac{4}{sin^2(x)} -\frac{4}{sin^2(x)} +\frac{3}{cos^2(x)}-0= \frac{3}{cos^2(x)}-\frac{4}{sin^2(x)}](https://tex.z-dn.net/?f=-%5Cfrac%7B4%7D%7Bsin%5E2%28x%29%7D%20%2B%5Cfrac%7B3%7D%7Bcos%5E2%28x%29%7D-0%3D%20%5Cfrac%7B3%7D%7Bcos%5E2%28x%29%7D-%5Cfrac%7B4%7D%7Bsin%5E2%28x%29%7D)